Psychometric properties of the exercise self-efficacy scale in patients with chronic obstructive pulmonary disease - Cristina Sacristán-Galisteo; Tamara del Corral; Ibai López-de-Uralde-Villanueva; M Carmen Gómez; Patricia Martín-Casas (PLoS ONE, 2025)
Objectives This study explores the psychometric properties of the Exercise Self-Efficacy (ESE) scale among individuals with Chronic Obstructive Pulmonary Disease (COPD). The secondary objective was to evaluate the relationship between self-efficacy, functional exercise capacity, health-related quality of life and psychological state in the same population. Methods This cross-sectional study was carried out in primary care centers in Spain. The sample was comprised of 156 people with COPD in whom anthropometric and clinical information was recorded. The ESE scale and other measures on functional exercise capacity, psychological state and health-related quality of life were administered. Psychometric properties were assessed through construct validity (EFA, exploratory factor analysis; CFA, confirmatory factor analysis), internal consistency, floor/ceiling effects and convergent validity. In this way, a quantitative, predictive and correlational research was carried out. Results The EFA ruled out the structure of a single factor (Barletts’s test p < 0.001, Kaiser-Meyer-Olkin 0.9). ACF suggested that the most appropriate adjustment model was the two-factor solution (comparative fit index = 0.967, Tucker–Lewis index = 0.961, root mean square approximation = 0.075, standardized root mean square residual = 0.058). Thus, ESE scale is best interpreting using 15 items distributed in 2 factors (“physical and occupational/environmental barriers” and “psychosocial barriers”) than explained to 56.7% of the variance. With regard to reliability, Cronbach’s alpha was = 0.92 and no floor or ceiling effects were observed. The scale showed a moderate/strong correlation with functional exercise capacity (r = 0.41), health-related quality of life (r= − 0.53) and psychological status (r= − 0.63). Conclusions The psychometric testing of the ESE scale provided support for the reliability and validity of the instrument in individuals with COPD. The ESE scale score shows a moderate positive correlation with functional exercise capacity and a negative correlation with health-related quality of life. In addition to a strong correlation with psychological status. In future research, the predictive power of the ESE scale in adherence to non-pharmacological treatment could be studied.